Identification of Key Immune-Related Genes in the Progression of Septic Shock - Niu, Jingjing; Qin, Bingyu; Wang, Cunzhen; Chen, Chao; Yang, Jianxu; Shao, Huanzhang (Frontiers in Genetics, 2021)
Objective Septic shock is the severe complication of sepsis, with a high mortality. The inflammatory response regulates the immune status and mediates the progression of septic shock. In this study, we aim to identify the key immune-related genes (IRGs) of septic shock and explore their potential mechanism. Methods Gene expression profiles of septic shock blood samples and normal whole blood samples were retrieved from the Gene Expression Omnibus (GEO) and Genotype-Tissue Expression Portal (GTEx). The differentially expressed genes (DEGs) and septic-shock-specific IRGs were evaluated and identified, along with the immune components by “cell type identification by estimating relative subsets of RNA transcripts (CIBERSORT, version x)” algorithm. Additionally, in order to explore the key regulatory network, the relationship among septic-shock-specific IRGs, upstream transcription factors (TFs) and downstream signaling pathways were also identified by the Gene Set Variation Analysis (GSVA) and co-expression analysis. Moreover, the Connectivity Map (CM) analysis was applied to find bioactive small molecules against the members of regulation network while Chromatin Immunoprecipitation sequencing (ChIP-seq) and Assay for Targeting Accessible-Chromatin with high-throughput sequencing (ATAC-seq) data were used to validated the regulation mechanism of the network. Results A total of 14,843 DEGs were found between 63 septic shock blood samples and 337 normal whole blood samples. Then, we identified septic-shock-specific 839 IRGs as the intersection of DEGs and IRGs. Moreover, we uncovered the regulatory networks based on co-expression analysis and found 28 co-expression interaction pairs. In the regulation network, PPP3CA may regulate estrogen response late, glycolysis and TNFa signaling via NFκB and HLA; KRAS may be related to estrogen response late and HLA; and TLR8 may be associated with TNFa signaling via NFκB. And the regulation mechanisms between TFs and IRGs (TLR8, PPP3CA and KRAS) were validated by ChIP-seq and ATAC-seq. Conclusion Our data identify three septic-shock-specific IRGs (TLR8, PPP3CA and KRAS) as candidate therapeutic targets for septic shock and provides constructed regulatory networks in septic shock to explore its potential mechanism.